2021
DOI: 10.1186/s13075-021-02431-z
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of association in HLA region with rheumatoid arthritis in a diverse Asian population: evidence from the MyEIRA case-control study

Abstract: Background Fine-mapping of human leukocyte antigen (HLA) region for rheumatoid arthritis (RA) risk factors has identified several HLA alleles and its corresponding amino acid residues as independent signals (i.e., HLA-A, HLA-B, HLA-DPB1, and HLA-DQA1 genes), in addition to the well-established genetic factor in HLA-DRB1 gene. However, this was mainly performed in the Caucasian and East Asian populations, and data from different Asian regions is less represented. We aimed to evaluate whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…The details of the classical HLA imputation for the dataset were previously described. 26 Briefly, a total of 6125 single nucleotide polymorphisms (SNPs) between position 29 and 34 Mb in the HLA region on chromosome 6 (GRCh37) were extracted from the postquality control Immunochip dataset. We imputed the classical two-digit and four-digit HLA alleles by using the extracted SNP genotypes from the HLA region, along with SNPs from the Pan Asian reference panel.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The details of the classical HLA imputation for the dataset were previously described. 26 Briefly, a total of 6125 single nucleotide polymorphisms (SNPs) between position 29 and 34 Mb in the HLA region on chromosome 6 (GRCh37) were extracted from the postquality control Immunochip dataset. We imputed the classical two-digit and four-digit HLA alleles by using the extracted SNP genotypes from the HLA region, along with SNPs from the Pan Asian reference panel.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the data from a large, well-characterised, population-based and ethnically matched normal controls for risk association testing with the SLE patient’s cohort 23 26. These normal individuals with Malay ethnicity were previously subjected to dense SNP genotyping using the Immunochip array (~196 000 SNP markers) 26. We then performed HLA imputation for classical HLA-DQA1, HLA-DPA1 and HLA-DPB1 genes for allelic association analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of Han Chinese ACPA-positive RA patients, strong association with Asp at position 160 of the HLA-DQA1 gene was detected independent from the HLA-DRB1 *04:05 allele and several other alleles from the HLA locus [ 38 ]. In an analysis of a multiethnic Malaysian cohort, a strong risk of ACPA-positive RA was associated with Val at position 11 of HLA-DRB1 ; it was found that HLA-DQB1 *03:02 allele was inversely related to the risk of developing ACPA-positive RA in the Malay population [ 39 ].…”
Section: Hla-related Genetic Associations In Rheumatoid Arthritismentioning
confidence: 99%